Quiz. Correct answer to the quiz. Check your diagnosis Hodgkin’s lymphoma mimicking tuberculosis in cervical lymph nodes - Szumera-Ciećkiewicz, Anna; Prochorec-Sobieszek, Monika; Lech-Marańda, Ewa (Polish Journal of Pathology, 2014)
The authors present a case description of an 81-year-old male with general symptoms (fever, night sweats, weight loss) and cervical/supraclavicular lymphadenopathy. The revised lymph node histopathological examination revealed nodular sclerosis classical Hodgkin’s lymphoma associated with abundant tuberculosis-mimicking granulomatous reaction. The diagnosis may be difficult due to similarities in clinical course, laboratory tests and imaging. The morphology of Hodgkin-Reed-Sternberg cells and the immunohistochemical profile are the most helpful in differential diagnosis. In cases where granulomas coexist with negative acid-fast staining, pathologists should always recommend evaluation of further and broader diagnostic procedures to exclude Mycobacterium tuberculosis infection.